2002
DOI: 10.1023/a:1020535415283
|View full text |Cite|
|
Sign up to set email alerts
|

Untitled

Abstract: We report here an unexpected difference in the solubilities of D- and L-tyrosine in water, which could be discerned by their rate of crystallization and the resulting concentrations of their saturated solutions. A supersaturated solution of 10 mM L-tyrosine at 20 degrees C crystallized much more slowly than that of D-tyrosine under the same conditions, and the saturated solution of L-tyrosine was more concentrated than that of D-tyrosine. Supersaturated solutions of 10 mM DL-tyrosine in water formed precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 14 publications
1
42
0
2
Order By: Relevance
“…By an accurate comparison of the spectral behavior of the two enantiomers, the occurrence of significant differences in these interactions has been excluded, leaving without a direct experimental evidence able to explain their different solubility in AOT micellar solution. Unless one wants to speculate about minute energy differences between the two enantiomers [22], one needs to consider the possibility of different amounts of water or chiral contaminant traces in the micellar solutions and/or recognition of a single AOT configuration.…”
Section: Discussionmentioning
confidence: 99%
“…By an accurate comparison of the spectral behavior of the two enantiomers, the occurrence of significant differences in these interactions has been excluded, leaving without a direct experimental evidence able to explain their different solubility in AOT micellar solution. Unless one wants to speculate about minute energy differences between the two enantiomers [22], one needs to consider the possibility of different amounts of water or chiral contaminant traces in the micellar solutions and/or recognition of a single AOT configuration.…”
Section: Discussionmentioning
confidence: 99%
“…A number of experimental techniques have been proposed for the observation of PV in molecular systems, including rovibrational 11 , electronic [12][13][14] , Mössbauer 15 and NMR 16 spectroscopy, as well as crystallization 17 and solubility 18 experiments, or optical activity measurements 19 , but no unambiguous observation has so far been made. After the pioneering work of Yamagata 1 , Rein 2 , and Gajzago and Marx 3 who first suggested that weak interaction is responsible for an energy difference in the spectrum of right-and left-handed chiral molecules, Letokhov proposed in 1975 to observe PV effects in molecules as a difference 11 After a first test on separated enantiomers of camphor in 1977 20 , the most sensitive experiments to date following Lethokov's proposal were performed around 2000 by authors of this paper.…”
Section: Introduction: Context and Historymentioning
confidence: 99%
“…Ramachandran and Natarajan [70] showed that L-tyrosine crystallizes in silica gel having spherulitic morphology with long needles. This is also true regarding the crystallization experiment of Shinitzky et al [27] (D. Deamer, personal communication). Dendritic pattern of liquid-crystal growth in organic materials is a common place [71].…”
Section: Justificationmentioning
confidence: 71%
“…Their data also show that crystalliza-tion of racemic D, L-Asn yielded preferential formation of L-crystals over D-crystals, the fact that was left unexplained. In essence, this is another manifestation of "unexpected difference between D-and L-" enantiomers discussed by Shinitsky et al [27].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation